2015
DOI: 10.1152/ajpendo.00447.2014
|View full text |Cite
|
Sign up to set email alerts
|

Liver protein profiles in insulin receptor-knockout mice reveal novel molecules involved in the diabetes pathophysiology

Abstract: It is under a complex control by substrates such as hormones, nutrients, and neuronal impulses. Insulin promotes glycogen synthesis, lipogenesis, and lipoprotein synthesis and inhibits gluconeogenesis, glycogenolysis, and VLDL secretion by modifying the expression and enzymatic activity of specific molecules. To understand the pathophysiological mechanisms leading to metabolic liver disease, we analyzed liver protein patterns expressed in a mouse model of diabetes by proteomic approaches. We used insulin recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…However, whether the dysfunction in the pathways regulating glycemic homeostasis triggers brain proteinaceous accumulation or vice versa is still not clear. What is known so far is that HTT is involved in both HD and T2DM (Capuani et al, 2015) and that this implication is further validated by present results.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…However, whether the dysfunction in the pathways regulating glycemic homeostasis triggers brain proteinaceous accumulation or vice versa is still not clear. What is known so far is that HTT is involved in both HD and T2DM (Capuani et al, 2015) and that this implication is further validated by present results.…”
supporting
confidence: 88%
“…By using a proteomic approach in a diabetic mouse model, we demonstrated a novel central role of huntingtin protein (HTT) in metabolism and in glucose homeostasis (Capuani et al, 2015). An expansion of the CAG (polyQ) repeats in the gene encoded for HTT caused HD, which is an orphan autosomal dominant disease leading to neuronal death (apoptosis), dementia, and movement disorders (Jimenez-Sanchez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the nature of the metabolic defects in zebrafish ins mutants, we probed the proteome of 108 hpf ins mutants compared to their WT siblings and assessed this dataset relative to seven other proteomes from diabetic tissues of rodent or human origin (Hwang et al, 2010; Mullen and Ohlendieck, 2010; Giebelstein et al, 2012; Valle et al, 2012); S.-J. Kim et al, 2014a; Capuani et al, 2015; Braga et al, 2016; Zabielski et al, 2016). Strikingly, pathways like gluconeogenesis, mitochondrial dysfunction, sirtuin signaling, and oxidative phosphorylation, which were affected in diabetic conditions across these studies, were similarly disrupted in zebrafish ins mutants (Figure 1F and supplementary file 1).…”
Section: Resultsmentioning
confidence: 99%
“…Soltis et al (2017) identified 362 significant differential proteins in the liver of mice fed with high-fat diet, and upregulated proteins played a part in fatty acid β-oxidation, fatty acid transport, and carbohydrate biosynthesis, the downregulated proteins were participated in cholesterol biosynthesis and urea cycle. Capuani et al (2015) thought that the differential proteins in the liver of insulin receptor-knockout mice were mainly involved in glycolipid metabolism and oxidative stress processes. Holper, Nolte, Bober, Braun, and Kruger (2015) found 407 significant regulatory proteins, which involved in fatty acid metabolism, PPAR signaling, and the degradation of branched chain amino acids (BCAAs).…”
Section: Differential Protein Profiles In Adipose Tissue Liver and Skeletal Muscle Under Irmentioning
confidence: 99%